2006
DOI: 10.1007/s10571-006-9035-y
|View full text |Cite
|
Sign up to set email alerts
|

Extract EGb 761 Pretreatment Limits Ubiquitin Positive Aggregates in Rabbit Spinal Cord Neurons after Ischemia-Reperfusion

Abstract: 1. Ubiquitin immunohistochemistry was used for investigation of time dependent changes of ubiquitin in the nerve cells reacting to ischemic/reperfusion damage. In the rabbit spinal cord ischemia model a period of 30 min ischemia followed by 24 and 72 h of reperfusion caused neuronal degeneration selectively in the ventral horn motor neurons as well as interneurons of the intermediate zone. 2. Ubiquitin aggregates were accumulated in the neurons of lamina IX and the neurons of intermediate zone destined to die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our previous study, we have demonstrated localization of protein ubiquitin, by ubiquitin immunohistochemistry, in the spinal cord neurons of rabbits pretreated with EGb 761 before 30 min of ischemia followed by 48 or 72 h of reperfusion (Mechírová et al 2006). In this present study, we completed ubiquitin distribution in the spinal cord neurons after noradrenalin preconditioning.…”
Section: Ubiquitin and Neun Immunohistochemistrymentioning
confidence: 55%
See 2 more Smart Citations
“…In our previous study, we have demonstrated localization of protein ubiquitin, by ubiquitin immunohistochemistry, in the spinal cord neurons of rabbits pretreated with EGb 761 before 30 min of ischemia followed by 48 or 72 h of reperfusion (Mechírová et al 2006). In this present study, we completed ubiquitin distribution in the spinal cord neurons after noradrenalin preconditioning.…”
Section: Ubiquitin and Neun Immunohistochemistrymentioning
confidence: 55%
“…Ubiquitin aggregates have never been visible. Ubiquitin aggregates are the signs of damaged, degenerated cells that have lost the ability of intracellular hydrolytic degradation of altered proteins (Mechírová et al 2006). In this study, we extended our previous results with the ubiquitin immunohistochemistry in the groups of animals with noradrenalin preconditioning, and also decided to use Fluoro Jade B fluorescent method for quantitative analysis of degenerated neurons in all our experimental groups.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2 The dosage and administration intervals of EGb in our study were similar to previous studies in the literature. In a study by Mechirova et al, 21 30 min of infrarenal aortic ischemia resulted in paraplegia in all test animals and 40 mg/kg of EGb for 7 days resulted in significant recovery from paraplegia. The study showed that the EGb had a protective effect against IR injury in the spinal cord.…”
Section: Discussionmentioning
confidence: 82%
“…Bilobalide component of EGb 761 increases the respiratory control ratio of mitochondria and protects against the uncoupling of oxidative phosphorylation, by this way increases ATP levels (DeFeudis 2002), influences cognitive deficits that follow stress or traumatic brain injury (DeFeudis and Drieu 2000). Positive effects of EGb 761 pretreatment on neurons after ischemia/reperfusion were confirmed by studies of global ischemia in the rats (Hrehorovska et al 2004;Domorakova et al 2006) or in the gerbils (Chandrasekaran et al 2002) and in the rabbit spinal cord ischemia (Mechirova and Domorakova 2002;Mechirova et al 2006). Less data were found about ischemia/reperfusion and EGb 761 posttreatment.…”
Section: Introductionmentioning
confidence: 96%